2020
DOI: 10.1108/jaee-11-2019-0214
|View full text |Cite
|
Sign up to set email alerts
|

Institutional complexity and CSR practices: evidence from a developing country

Abstract: PurposeThe study aims to investigate the appearance of corporate social and environmental responsibility (CSER) practices in a context where economic, communal and political institutions are highly central and competing with each other.Design/methodology/approachTheoretically, the study draws upon the institutional logics perspective and the theoretical concepts of logics centrality and compatibility to understand how higher-order institutions interact with mundane CSER practices observed at the case company's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 108 publications
(150 reference statements)
2
30
0
Order By: Relevance
“…Moreover, the founding father in the field of CSR, Carroll [9], has also placed this responsibility as core to his CSR model. The studies from developing countries have produced mixed results for this domain, for example, the studies of Diab and Metwally [63] and Mohammed and Rashid [16] did confirm the importance of economic CSR, whereas the study of Hassan and Nareeman [64] did not confirm it from the perspective of consumers. In a nutshell, the SMEs in Pakistan are well concerned with their economic responsibility, and the results revealed that this is the second most important factor for the SMEs in Pakistan.…”
Section: Economic Dimension Of Csrmentioning
confidence: 99%
“…Moreover, the founding father in the field of CSR, Carroll [9], has also placed this responsibility as core to his CSR model. The studies from developing countries have produced mixed results for this domain, for example, the studies of Diab and Metwally [63] and Mohammed and Rashid [16] did confirm the importance of economic CSR, whereas the study of Hassan and Nareeman [64] did not confirm it from the perspective of consumers. In a nutshell, the SMEs in Pakistan are well concerned with their economic responsibility, and the results revealed that this is the second most important factor for the SMEs in Pakistan.…”
Section: Economic Dimension Of Csrmentioning
confidence: 99%
“…This mode of governing characterises the world by increasing institutional connectedness and interdisciplinary relations, which produces demand multiplicity within organisations. This multiplicity has produced three related phenomena in the logics literature: institutional complexity (Diab and Metwally, 2020;Greenwood et al, 2011), institutional pluralism (Kraatz and Block, 2008) and institutional hybridity (Pache and Santos, 2013). The presence of competing logics as a result of logics multiplicity is a central issue in the literature (Besharov and Smith, 2014).…”
Section: Institutional Logics Literaturementioning
confidence: 99%
“…There is a dearth of extant empirical research from developing countries, pertaining to environmental and social accounting and disclosure in general (Adhariani and du Toit, 2020;Belal, 2001;Belal and Cooper, 2011;Diab and Metwally, 2020;Gerged et al, 2020a;Welbeck et al, 2020). For instance, most extant disclosure studies are focused upon developed countries such as Australia, the United Kingdom and Europe (See Robert, 1991;Gray et al, 1995;Deegan and Gordon,1996;Deegan et al, 2002;Campbell, 2004;Cowan and Gadenne, 2005;Rao et al, 2012;Burgwal and Vieira, 2014;Yu and Zhao, 2015;Albitar et al, 2020) and upon emerging economies such as Malaysia, Hong Kong and China (e.g., Gao et al, 2005;Smith et al, 2007;Qu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%